Detection and monitoring system material rack location in warehouse using internet of things - Hamonangan, Dedy; Tio Ramadhan, Rizki; Arifiansyah, Rafli; Bahtiar, Ajis (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Internet of Things (IoT) is now a technology that is changing the way we live and work in an increasingly digital era. The IoT is a way to connect and communicate with real-world objects. In the modern era, IoT entered a modern era called Industry 4.0. PT. Doellken Bintan manually checked the material shelves one by one until they found the material they were looking for. Materials used at PT. Doellken Bintan are available in various types, the spacious warehouse structure and multi-story material racking model makes it less efficient. In this design, the system is connected to the internet and users can access this system by smartphone. This equipment uses the Esp8266 MCU node to read commands from a smartphone, then sends data bytes to the Arduino Mega 2560 to turn on the LED light as an indicator of the position of the shelf being searched. The final results show that this project can work well where the user can change the amount of material stock on the smartphone application according to the actual amount on the material shelf in the warehouse and can detect the location of the material on the shelf from the user's smartphone with a time delay which is influenced by speed of internet network.